PENGEMBANGAN MODUL EDUKASI UNTUK MENGATASI PERILAKU PROKRASTINASI AKADEMIK PADA SISWA SEKOLAH MENENGAH PERTAMA (SMP) - Dilla Febryana; Elni Yakub; M. Arli Rusandi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to develop an educational module to overcome academic procrastination behavior in junior high school students. The research method used is research development (Research and Development) concerning the flow of R&D level 1 steps. The instrument used is a validation questionnaire which is validated by 5 material experts, three BK lecturers, and two BK teachers. The assessment module is reviewed from the physical or appearance aspect, the preliminary aspect, the content aspect, the summary aspect, the task/evaluation/assessment aspect, and the utilization aspect. The results of the study indicate that the development of an educational module has been implemented to overcome the behavior of academic procrastination in Junior High School students through 5 stages, namely through: potentials and problems; Collection of data or information; Product design; Design validation; Proven design. Of the five stages, an educational module has been produced to overcome academic procrastination behavior in junior high school students in terms of the physical aspect or appearance can be categorized as feasible, the preliminary aspect can be categorized as feasible, the content aspect can be categorized as feasible, the summary aspect can be categorized as feasible, the task/evaluation/assessment aspect can be categorized as feasible and the utilization aspect can be categorized as feasible. The best advice that can be given in this study is, for BK teachers it is expected before using this module to do an information service about the procrastination module. In hopes of detracting procrastination behavior on junior high school students. While the suggestion for the following researchers is to perform an effective test of this module to reduce academic procrastination in junior high school students (SMP).Key Words: education module, R&D, academic procrastination